Extraction of drainage Characteristics and Morphometric analysis using GIS and SRTM Digital Elevation Model Data in Sathyavedu area, Chittoor District, Andhra Pradesh, India - Golla Veeraswamy; Etikala Balaji; P. Harish (International Journal of Research in Informative Science Application & Techniques (IJRISAT), 2022)
The aim of the present study is to extraction of the drainage characteristics from SRTM 30M resolution data processed in Arc GIS 10.1and develops the different maps such as Drainage fill, flow accumulation, stream link, flow direction, stream order map. The study area stream order map shows 5 orders. Most of the stream area flow in the direction of North West to south west and it determine the less porosity and permeability due to presence of the granite schist, quartzite's and laterite group of rocks and SRTM DEM with spatial resolution of 30m.